Transcatheter aortic valve implantation – update and evidence. Issue 5 (3rd September 2015) - Van Linden, Arnaud; Doss, Mirko; Arsalan, Mani; Kim, Won Keun; Walther, Thomas
Abstract: Transcatheter aortic valve implantation (T-AVI) has become the standard of care for high-risk patients suffering from severe aortic valve stenosis. More than 60, 000 implants have been performed to date. While the first-generation T-AVI devices had some specific issues, the advancements in these first-generation devices and the development of second-generation devices significantly reduced the incidence of peri-procedural complications. The two major access routes are the transfemoral (TF) and the transapical (TA) approach. Both approaches have their advantages and should be considered equal alternatives for finding the best treatment option for the individual patient. Currently there are discussions about extending the indication to patients with lower risk profiles. However, there is no real evidence to justify an expansion, as results of surgical aortic valve replacement in low and intermediate risk patients are excellent.